2019
DOI: 10.1016/j.toxrep.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

ROS mediated antibacterial activity of photoilluminated riboflavin: A photodynamic mechanism against nosocomial infections

Abstract: HighlightsRiboflavin undergoes intersystem conversion under photoillumination.Interacts with molecular oxygen and generates ROS.Generated ROS disrupts E. coli cell membranes.Ultimately killing E. coli.Mechanism can be used to kill E. coli on hospital ware causing nosocomial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 40 publications
(41 reference statements)
0
33
0
Order By: Relevance
“…Recently, interest in silicon carbide films as a promising material for nanoelectronics and Riboflavin (vitamin B2) is an important and necessary drug for the development and viability of the human body. Vitamin preparation is used in the form of powders, and in the form of aqueous solutions [1,2]. Self-assembly is a process in which only the components of the final structure are involved [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest in silicon carbide films as a promising material for nanoelectronics and Riboflavin (vitamin B2) is an important and necessary drug for the development and viability of the human body. Vitamin preparation is used in the form of powders, and in the form of aqueous solutions [1,2]. Self-assembly is a process in which only the components of the final structure are involved [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of literature has confirmed that RF has an excellent antioxidant property that can be taped to nullify the toxic effects of many xenobiotics and drugs [14,27,29,30]. PB-induced toxicities because of its extensive usage in edibles, drinking water, colas, paints, and cosmetics are one of the profound clinical challenges in society.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Santos De Souza et al [48] and De Souza Queiroz et al [49] in separate studies on different cell lines reported induction of Fas-FasL-mediated apoptosis by RF under photoillumination. Recently, Khan et al [30] have shown that the photoactivated vitamin caused cell death in mice with lung carcinoma. It is noteworthy that the vitamin is a strong antioxidant in its native form, but it can also act as a prooxidant under photoillumination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of ROS in PBS was estimated using the 2',7'-dichlorofluorescin diacetate (DCFH-DA) method [29,30]. To achieve the adsorption/desorption equilibrium, polished and nanosecond laser irradiated Zr-BMG samples were immersed in a bacterial solution (0.01 mol/L PBS with 10 7 cfu/mL S. aureus ) for 24 h and then incubated with 500 μL of 2',7'-dichlorofluorescin diacetate (DPBF) solution (10 mM dissolved in DMSO) in the dark for 5 min.…”
Section: Antibacterial Characterization 231 Detection Of Rosmentioning
confidence: 99%